Kurt Vonnegut drawings - Vonnegut, Kurt 1922-2007 (Monacelli Press, 2014)
Those who know Kurt Vonnegut as one of America's most beloved and influential writers will be surprised and delighted to discover that he was also a gifted graphic artist. This book brings together the finest examples of his funny, strange, and moving drawings
Includes bibliographical references
Introduction. My father, the doodler / Nanette Vonnegut -- Essay. The remarkable artwork of Kurt Vonnegut / Peter Reed -- Drawings & texts. Self-portraits ; Abstraction ; Women ; Letters ; People ; Faces ; Looking at things ; Lines ; Things ; Words
Keywords: Vonnegut, Kurt; Vonnegut, Kurt -- 1922-2007; Drawing, American; Authors as artists / United States; Malerei; USA